Marital Status Transitions and Domestic Labour - Hewitt, B; Haynes, M; Western, M; Baxter, Janeen (Institute for Social Science Research & School of Social Science, The University of Queensland, 2010)
Using longitudinal survey data to investigate relationships between women’s time on domestic labour and transitions through partnerships and marriage. •It is well-known that pathways through the lifecourse have changed in recent years. •These changes have consequences for understanding the organisation of domestic work. •Important because research has shown that prior relationship experiences and events will affect the ways in which individuals and couples organise domestic labour in their current households.
Keywords: Families -- Partners; Human Capital -- Labour; Beliefs and Values -- Housework; Families and relationships; Lifestyle; Beliefs and Values; Families; Human Capital; Housework; Partners; Labour; Lifestyle; Families and relationships